INTERNATIONAL TOURISM: MODERN TRENDS, MODELS AND PROCESSES - Vico, Roberto Paolo (Sociedade e Território, 2018)
In a world and travel universe subject to continuous change, the tourism industry is under ever greater pressure to evolve and respond to the world it inhabits - in order to survive. The object of the paper is to discuss and analyze, some of the important issues and trends relating to tourism industries. In particular, ways in which the industry and its consumers are being affected and affecting these trends. The first two sections deploy elements of a steep analysis in order to detect significant demographic and macro political forces affecting tourism industries. Section three considers the “day-to-day…sphere” of travel and tourism, its ‘microenvironment’ and the competitive industry and markets forces they encounter there. The paper reviews one of the most significant micro trends affecting the airline sector: the dynamic growth of low cost carriers. The last part of this work looks into strategic and analytic models associated with tourism, highlighting some of the strategic directional trends being adapted to tourism sectors and into new collaborative forms of social media, communications and marketing.